A Simple Critical Response Evaluation Method for Base-Isolation Building-Connection Hybrid System Under Double Impulse as Representative of Near-Fault Ground Motion - Nakamura, Tomoya; Fujita, Kohei; Takewaki, Izuru (Frontiers in Built Environment, 2021)
A unique building system including a base-isolation, building-connection hybrid control system is revisited. The base-isolation system withstands pulse-type earthquake ground motions effectively and the building-connection system resists long-duration earthquake ground motions efficiently. A simple smart critical response evaluation method without nonlinear time-history response analysis is proposed for this hybrid building system under near-fault ground motions. An analytical expression of the maximum elastic-plastic deformation of a damped bilinear hysteretic single-degree-of-freedom (SDOF) model under the critical double impulse as a representative of pulse-type ground motions derived in the previous paper plays an important role in the development of the simple critical response evaluation method. A two-step transformation procedure into an SDOF model is proposed. The first step is the transformation of the main base-isolated building into an SDOF system and the second step is the reduction of the connecting dampers supported on a sub building to a damper with a sophisticated compensation factor on an assumed rigid wall. The evaluation of damping coefficients with the consideration of yielding of the base-isolation story is a key step in this paper. Different from the previous work, the equivalent damping coefficient is derived depending on the response range before and after yielding of the base-isolation story. This treatment certainly enhances the accuracy of the proposed method. The accuracy and reliability of the proposed response evaluation method is demonstrated by the time-history response analysis of the multi-degree-of-freedom (MDOF) model.